Synthesis of TiO2-incorporated activated carbon as an effective Ion electrosorption material. - Nasser A M Barakat; Yasmin T Sayed; Osama M Irfan; Marawa M Abdelaty (PLoS ONE, 2023)
Efficient, chemically stable and cheap materials are highly required as electrodes in the ions-electrosorption-based technologies such as supercapacitors and capacitive deionization desalination. Herein, facile preparation of titanium oxide-incorporated activated carbon using cheap precursors is introduced for this regard. The proposed material was synthesized using the solubility power of the subcritical water to partially dissolve titanium oxide particles to be adsorbable on the surface of the activated carbon. Typically, an aqueous suspension of commercial TiO2 particles (P25) and activated carbon was autoclaved at 180°C for 10 h. The physiochemical characterizations indicated high and uniform distribution of the inorganic material on the surface of the activated carbon. The ionic electrosorption capacity was highly improved as the specific capacitance increased from 76 to 515 F/g for the pristine and modified activated carbon, respectively at 5 mV/s in 0.5 M sodium chloride solution. However, the weight content of titanium oxide has to be adjusted; 0.01% is the optimum value. Overall, the study introduces novel and simple one-pot procedure to synthesis powerful titanium oxide-based functional materials from cheap solid titanium precursor without utilization of additional chemicals.